ANALISIS FAKTOR YANG MEMENGARUHI OSTEOPOROSIS PADA IBU MENOPAUSE DI WILAYAH KERJA PUSKESMAS STABAT KABUPATEN LANGKAT TAHUN 2019 - Ira Syafira; Razia Begum Suroyo; Tri Niswati Utami (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
Osteoporosis is a condition or disease in which bones become fragile and easily cracked or broken. Based on medical record data obtained in 2015, 106 cases of osteoporosis were found in menopausal and elderly women. This study aims to determine and analyze the effects of age, physical activity, smoking, family history, history of fractures on osteoporosis in menopausal mothers. The method used was the mix methods research method with a sequential Explanatory research model with a quantitative sample of 87 respondents and informants on a qualitative approach that was 10 menopausal women and health workers. Data collection techniques using questionnaires and research interview instruments. Data analysis was a multivariate analysis using the binary logistic test. The results indicated that there was an effect between age from the results of statistical tests of .044 <.05, physical activity of .012 <.05, family history of .014 <.05 and history of fracture of .035 <.05, the smoking variable of .223 > .05. The most dominant variable has an influence that was the family history variable with an OR value of 36.869. The conclusion shows that there is an influence between the age of physical activity, family history and history of fractures on osteoporosis in menopausal women but the smoking variable has no effect on osteoporosis in menopausal mothers. It is hoped that this research can be an input for health centers in managing osteoporosis and can improve the management of osteoporosis prevention programs with health promotion efforts. Keywords: Osteoporosis, Age, Physical Activity, Smoking, Family History, Fracture History